Pajak Terutang PPh 21 Pegawai Tidak Tetap Mitra Driver Gojek dan Maxim - Kowi, Yustina (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
The scope of the quantitative research approach is the calculation of PPh 21 objects and subjects of gojek and maxim driver partners in Jayapura City. There has been no empirical research on the extensification of PPh 21 tax objects for driver partners. The research objective measures the value of tax payable PPH 21 for gojek and maxim driver partners. The research population is known to be ± 981 active registered partners, the research sample size method with variance data as many as 203 (respondents), questionnaire data collection methods, data analysis methods with descriptive statistics, the stages of analysis are: (1) tabulation of questionnaire criteria for non-permanent employees (2) determination of tax withholding rates (3) cumulative calculation (4) calculation of PTKP (5) calculation of taxable income (6) measurement of Income Tax 21 payable. The results of this study, the average gross income of gojek driver partners Rp.5,054,634, / month and maxim Rp.5,219,835, - / month, the existence of 8 hours of work / day actually payable tax PPh 21 / month gojek driver partners interval Rp.8,350, - s.d Rp.340,400, - and maxim interval Rp.10,000, - s.d Rp.325,000. Gojek and Maxim have an Income Tax 21 responsibility to the Jayapura City Government, based on the economic deterrence model and compliance with the tax laws of Jayapura City PERDA No.33/2023; PMK No.168/2023; PP No.58/2023; Law No.7/2021; Law No.36/2008.